Uberworked and underpaid: how workers are disrupting the digital economy - Scholz, Trebor (Cambridge, 2016)
"This book is about the rise of digital labor. Companies like Uber and Amazon Mechanical Turk promise autonomy, choice, and flexibility. One of network culture's toughest critics, Trebor Scholz chronicles the work of workers in the "sharing economy," and the free labor on sites like Facebook, to take these myths apart. In this rich, accessible, and provocative book, Scholz exposes the uncaring reality of contingent digital work, which is thriving at the expense of employment and worker rights. The book is meant to inspire readers to join the growing number of worker-owned "platform cooperatives," rethink unions, and build a better future of work. A call to action, loud and clear, Uberworked and Underpaid shows that it is time to stop wage theft and "crowd fleecing," rethink wealth distribution, and address the urgent question of how digital labor should be regulated and how workers from Berlin, Barcelona, Seattle, and Sao Paulo can act in solidarity to defend their rights."